2018
DOI: 10.1002/icd.2098
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of theory‐of‐mind acquisition in Turkish children from diverse social backgrounds

Abstract: We examined the sequence of theory of mind (ToM) acquisition in 260 Turkish children (M age = 53.36 months, SD = 10.37) and the demographic factors associated with it. Children came from 5 different cities in Turkey. Their ToM skills were measured using ToM Scale, which probes Highlights• We assessed theory of mind (ToM) acquisition in 260 Turkish children whose families spanned a large range of social class circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 57 publications
3
30
0
1
Order By: Relevance
“…The developmental order in ToM skills acquisition has been addressed in previous studies (Hughes et al, 2011;Jenkins & Astington, 1996;Miller, 2009;Wellman et al, 2001). Furthermore, the present study showed that Turkish preschoolers gain ToM skills in the sequence of DD, KA, DB, FB, RAE, similar to children in Eastern societies (Selcuk et al, 2018;Shahaeian et al, 2011;Wellman et al, 2006) but different from those in Western societies (Kristen et al, 2006;Shahaeian et al, 2011). Cultural variances between the ToM sequence of acquisition can be interpreted to reflect on parents' child rearing values, practices, social rules, and expectations in collectivist vs. individualist societies (Shahaeian et al, 2011;Wellman et al, 2006).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The developmental order in ToM skills acquisition has been addressed in previous studies (Hughes et al, 2011;Jenkins & Astington, 1996;Miller, 2009;Wellman et al, 2001). Furthermore, the present study showed that Turkish preschoolers gain ToM skills in the sequence of DD, KA, DB, FB, RAE, similar to children in Eastern societies (Selcuk et al, 2018;Shahaeian et al, 2011;Wellman et al, 2006) but different from those in Western societies (Kristen et al, 2006;Shahaeian et al, 2011). Cultural variances between the ToM sequence of acquisition can be interpreted to reflect on parents' child rearing values, practices, social rules, and expectations in collectivist vs. individualist societies (Shahaeian et al, 2011;Wellman et al, 2006).…”
Section: Discussionsupporting
confidence: 70%
“…In line with this finding, other studies had gender-neutral findings regarding young children's ToM abilities (Altun, 2018;Carr et al, 2018;Devine & Hughes, 2016;Wellman & Liu, 2004). However, the limited number of studies conducted with Turkish preschoolers (Sarı & Altun, 2018;Selcuk et al, 2018) found that girls outperformed the boys in ToM tasks, but also that the gender differences are more likely to be reported in older children with regard to socialization and gender roles (Calero, Salles, Semelman, & Sigman, 2013;Devine & Hughes, 2016).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Most notably, it has been shown that children from mainland China and US are similar in timing of FB achievement as compared to children from Hong Kong who show success in FB tasks later (Liu et al 2008). In addition, it is now a well-documented finding that children from China, Iran, and Turkey master knowledge access tasks before diverse belief tasks, this is the reverse sequence when compared to American and Australian children (Selcuk et al 2018;Shahaeian et al 2011;Wellman et al 2006). TT acknowledges that folk psychologies, parenting practices, and societal expectations are the likely reasons for such differences.…”
Section: The Effect Of Child-directed Language On Tom Developmentmentioning
confidence: 99%